Comparing men`s soccer head impact characteristics over a three year time period - Ennis, K. M.; Bradney, D. A.; Breedlove, K. M.; Bowman, T. G. (Journal of Athletic Training, 2019)
Context: Head impacts are a concern in sports due to potential short term and long term negative health effects. By studying head impacts over multiple seasons, injury patterns may be recognized which can lead to rule changes within the sport and other injury reduction measures. To date, most literature has focused on women`s soccer and other sports compared to men`s soccer. The objective was to compare head impact characteristics (impact location and mechanism) in men`s soccer over 3 years. Methods: We completed a descriptive epidemiology study on male collegiate soccer teams over three fall seasons (53 games, 94 practices). Participants included 26 NCAA Division III intercollegiate male soccer players (age = 19.64 ± 1.25 years, height = 181.70 ± 5.80 cm, mass = 76.98 ± 10.19 kg). Participants wore X2 Biosystem xPatch sensors that recorded frequency, location, and magnitude of head impacts over a 10 g threshold. All head impacts were confi rmed through time-stamped video analysis. We determined frequency differences by calculating the incidence rates (IRs) per 1000 athlete-exposures (participation in a practice or game for any amount of time) and the incidence rate ratios (IRRs) with corresponding 95% confi dence intervals (CI95). A MANOVA was used to identify magnitude differences for linear acceleration (g) and rotational acceleration (deg/sec2). Results: The overall male soccer player IR was 7.50/1000 athlete-exposures (CI95= 2.85-12.15). The most common mechanism for a head impact was ball to head (IR = 441.86, CI95 = 406.18- 477.55), and the most common location on the head for an impact was to the side of the head (IR = 478.62, CI95 = 441.48-515.76). The interaction between mechanism and impact location (F18,2254=1.97, P=.008, n2=1.6) and the main effect for location (F6,2254=3.29, P<.01, n2=.9) were statistically signifi cant. The main effect for mechanism was not signifi cant (F10,2254=1.03, P=.419, n2=.5, 1-ß=.553). Follow-up ANOVAs showed signifi cant interactions between mechanism and location for linear (F9,1128=1.97, P=.040, n2=1.5) and rotational (F9,1128=2.95, P<.01, n2=2.3) accelerations. Main effects were signifi cant for location when analyzing linear (F3,1128=3.01, P=.029, n2=.8) and rotational F3,1128=6.3, P<.001, n2=1.6) accelerations as well. The main effect for mechanism when analyzing linear (F5,1128=.248, P=.941, n2 =.1, 1-ß=.111) and rotational (F5,1128=.392, P=.855, n2 =.2, 1-ß=.154) accelerations were not signifi cant. Post hoc results revealed no signifi cant pairwise differences (P>.05). Conclusions: The IR for head impacts in our study of men`s soccer players is lower than head impact IRs reported previously in women`s soccer players and other sports. We speculate that these differences may be due to different levels of body control between sexes and differences between soccer and other contact sports. Head impact prevention efforts should be focused on impacts to the side of the head, the most common location in our data, and ball to head impacts, the most common mechanism, potentially through manipulation of player behavior.